2010
DOI: 10.1007/s10811-010-9607-6
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic antioxidant response to low-temperature acclimation in the cyanobacterium Arthrospira platensis

Abstract: Changes in antioxidant enzyme activities in response to low-temperature-induced photoinhibition were investigated in the two strains of the cyanobacterium Arthrospira platensis, Kenya and M2. When transferred to 15 degrees C from 33 degrees C, cells exhibited an immediate cessation of growth followed by a new acclimated growth rate. Although both strains had similar growth rates at 33 degrees C, once transferred to a lower temperature environment, Kenya had a faster growth rate than M2. There were variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For example, homeoviscous adaptation, which involves the induction of polyunsaturated fatty acids synthesis at Low temperature (LT), plays a significant role in cold adaptation in cyanobacteria, including Spirulina [16,17]. Lee-Feng et al [18] demonstrated that enhanced antioxidant enzyme activities at LT (15°C) are an efficient regulatory strategic response to LT-induced photoinhibition. In addition, a previous study also indicated that the adaptation of Arthrospira platensis to cold stress involves a down-regulation of photosynthetic activity and increased resistance to photoinhibition [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, homeoviscous adaptation, which involves the induction of polyunsaturated fatty acids synthesis at Low temperature (LT), plays a significant role in cold adaptation in cyanobacteria, including Spirulina [16,17]. Lee-Feng et al [18] demonstrated that enhanced antioxidant enzyme activities at LT (15°C) are an efficient regulatory strategic response to LT-induced photoinhibition. In addition, a previous study also indicated that the adaptation of Arthrospira platensis to cold stress involves a down-regulation of photosynthetic activity and increased resistance to photoinhibition [19].…”
Section: Introductionmentioning
confidence: 99%
“…Increased activities of SOD, CAT, APX (ascorbate peroxidase), and GR provide protection against heat (43°C) stress in Anabaena doliolum Bharadwaja . The greater acclima-tion ability of Arthrospira platensis Kenya to low temperature (15°C) is related to the higher activity of SOD, CAT, DHAR (dehydroascorbate reductase), GR, and the induction of a higher number of SOD isoenzymes in this strain, as compared to A. platensis M2 (Chien & Vonshak 2011).…”
Section: Discussionmentioning
confidence: 82%
“…). The greater acclimation ability of Arthrospira platensis Kenya to low temperature (15°C) is related to the higher activity of SOD, CAT, DHAR (dehydroascorbate reductase), GR, and the induction of a higher number of SOD isoenzymes in this strain, as compared to A. platensis M2 (Chien & Vonshak ).…”
Section: Discussionmentioning
confidence: 84%
“…2016). The main role of antioxidants is to reduce the levels of harmful reactive oxygen species (ROS) which are produced as a result of stress and consequently prevent the damage of cellular membranes by lipid peroxidation (Chien and Vonshak 2011; Ara et al . 2013; Song et al .…”
Section: Introductionmentioning
confidence: 99%